2017
DOI: 10.1016/j.jarmac.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval-enhanced suggestibility: A retrospective and a new investigation.

Abstract: Eyewitnesses are often repeatedly interviewed about the same crime, and they might be exposed to misleading information between these interviews. Taking a memory test before being exposed to misinformation can ironically increase the likelihood that an eyewitness would fall prey to the misinformation effect-a finding termed Retrieval-Enhanced Suggestibility (RES). In this paper, we outline the motivation behind the original research on RES, summarize the theoretical explanations that have been used to explain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 64 publications
1
43
0
Order By: Relevance
“…For example, learners reported that they were more likely to use deeper encoding strategies when relearning previously studied materials after a test trial than after a restudy trial (Soderstrom & Bjork, 2014). Further, taking a test can alter how participants distribute their encoding or attentional resources during subsequent encoding opportunities (Chan, Manley, & Lang, 2017;Gordon & Thomas, 2014;Jing et al, 2016;Szpunar et al, 2013). For example, in a recent study using a triad learning paradigm (Davis & Chan, 2015; see also Finn & Roediger, 2013), participants first studied a set of face-name pairs.…”
Section: A Strategy Change Perspective Of Test-potentiated New Learningmentioning
confidence: 99%
“…For example, learners reported that they were more likely to use deeper encoding strategies when relearning previously studied materials after a test trial than after a restudy trial (Soderstrom & Bjork, 2014). Further, taking a test can alter how participants distribute their encoding or attentional resources during subsequent encoding opportunities (Chan, Manley, & Lang, 2017;Gordon & Thomas, 2014;Jing et al, 2016;Szpunar et al, 2013). For example, in a recent study using a triad learning paradigm (Davis & Chan, 2015; see also Finn & Roediger, 2013), participants first studied a set of face-name pairs.…”
Section: A Strategy Change Perspective Of Test-potentiated New Learningmentioning
confidence: 99%
“…For example, it has been demonstrated using various stimuli (Butler & Loftus, 2017;Chan, Wilford, & Hughes, 2012), in children (Brackmann, Otgaar, Sauerland, & Howe, 2016), younger and older adults (Chan et al, 2009), with repeated tests (Chan & LaPaglia, 2011), and in free and cued recall initial tests (Wilford, Chan, & Tuhn, 2014). A proposed explanation for retrieval-enhanced suggestibility is that the initial test inadvertently enhanced learning of the misinformation (Chan, Manley, & Lang, 2017;Thomas et al, 2010). Specifically, a wealth of research has shown that retrieval has both a backward and forward effect on learning.…”
Section: Retrieval-enhanced Suggestibilitymentioning
confidence: 99%
“…When participants are confronted with misinformation, details related to the initially tested material capture their attention and become better encoded. This increased encoding of the misinformation in turn eases its retrieval during the final test, leading to retrieval-enhanced suggestibility (for a review, see Chan et al, 2017).…”
Section: Retrieval-enhanced Suggestibilitymentioning
confidence: 99%
“…Exposure to misinformation can have detrimental effects on eyewitness memory accuracy (Loftus, 2005;Zaragoza, Belli, & Payment, 2006). Although one might expect that asking witnesses to provide an initial statement (i.e., engage in retrieval practice) might inoculate them against suggestive misinformation later (Pansky & Tenenboim, 2011), it sometimes has the opposite effect-a phenomenon known as retrievalenhancedsuggestibility (RES; Chan et al, 2017;Chan, Thomas, & Bulevich, 2009). In the RES paradigm, participants view a target event and then receive an initial memory test over that event (initially tested) or not (nontested).…”
mentioning
confidence: 99%
“…Consequently, the tested participants are more likely to discount their own memory and instead report the information provided in the postevent narrative. In a review of the RES literature, Chan et al (2017) referred to this account as the misinformation acceptance hypothesis-a term borrowed from the classic misinformation effect literature (Belli, 1989), according to which the misinformation effect occurs because subjects accept and believe that the misinformation appeared in the witnessed event. In this particular application of the misinformation acceptance account, retrieval is hypothesized to increase suggestibility not because it enhances learning of the misinformation (as suggested by the TPL account), but because it increases the perceived accuracy of the misinformation.…”
mentioning
confidence: 99%